The double deficit of the USA and disequilibria in the world economy - Werner Kamppeter (Intereconomics, 1988)
The disequilibria in the world economy, of which the massive trade and current account deficits of the USA are but one manifestation, have reached dangerous proportions. The following article presents a number of scenarios to show how they may develop in future.
Keywords: 330